Multisegment integration technique for post-buckling analysis of a pinned-fixed slender elastic rod - Banu, Sajeda; Saha, Goutam; Saha, Sumon (BRAC University, 2010)
This paper investigates the post-buckling behavior of a slender axially inextensible elastic rod with pinned-fixed end. The set of five first order nonlinear ordinary differential equations with boundary conditions specified at both ends constitutes a complex two point boundary value problem. By using multisegment integration technique, the highly nonlinear boundary value problems are numerically solved. Results are presented in non-dimensional graphs for a range of prescribed loading condition. The secondary equilibrium paths and the post-buckling configurations of the rod are presented.